2021
DOI: 10.1055/a-1524-0358
|View full text |Cite
|
Sign up to set email alerts
|

Phytogenic Compounds for Enhancing Intestinal Barrier Function in Poultry–A Review

Abstract: After the European Union ban of antibiotic growth promoters, works on different methods of improving gut health have intensified. The poultry industry is struggling with problems that were previously controlled by antibiotic growth promoters, therefore the search for optimal solutions continues. Simultaneously, there is also increasing social pressure to minimize the use of antibiotics and replace them with alternative feed additives. A variety of available alternatives is considered safe by consumers, among w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 182 publications
(376 reference statements)
0
5
0
Order By: Relevance
“…The beneficial effects of PFAs on intestinal physiology comprise a lower crypt depth that might be perceived as less interaction with various stressors, a diminished adverse reaction and lower sloughing (Kamboh & Zhu, 2014). PFAs have several advantages for an animal, including better palpability, an energizing impact on gastrointestinal activity, general intestinal morphology enhancement and better meat quality (Latek et al, 2022). The main ways by which PFAs have a beneficial impact on intestinal morphology are their ability to reduce inflammation and promote cellular growth, although mortality control may also be related (Patra et al, 2019).…”
Section: Pfas On Gut Barrier Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…The beneficial effects of PFAs on intestinal physiology comprise a lower crypt depth that might be perceived as less interaction with various stressors, a diminished adverse reaction and lower sloughing (Kamboh & Zhu, 2014). PFAs have several advantages for an animal, including better palpability, an energizing impact on gastrointestinal activity, general intestinal morphology enhancement and better meat quality (Latek et al, 2022). The main ways by which PFAs have a beneficial impact on intestinal morphology are their ability to reduce inflammation and promote cellular growth, although mortality control may also be related (Patra et al, 2019).…”
Section: Pfas On Gut Barrier Functionmentioning
confidence: 99%
“…Optimizing the manufacturing process to be effective and eco‐friendly for consumers is currently a formidable challenge for scientists, veterinarians, producers and researchers. The swine and poultry industries confront difficulties maintaining animal health in consideration of the prohibition of utilizing in‐feed antibiotics in response to increasing public concerns about the development of antimicrobial organisms in both animals and humans (Latek et al, 2022). Consumers perceive a range of alternatives as secure, and phytogenics are a vital component of those alternatives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of bioactive compounds (natural additives) in poultry feed is among the investigated potential alternatives to the antibiotic-based approach. Such additives might improve certain aspects of avian wellbeing and provide final products that are safe for consumers 20 , 21 . One phytogenic substance that exhibits the potential to beneficially modulate gut health and functionality is cannabidiol (CBD) obtained from hemp, which has recently attracted considerable attention.…”
Section: Introductionmentioning
confidence: 99%
“…Many published treatises reported that the pure kinds of PAF and their various mixture had been applied in several in vivo and in vitro researches to uncover the immunomodulatory plausible, antibacterial, anthelmintic, coccidiostat, anti-inflammatory, antiviral, and antioxidant possessions (Oladeji et al, 2019;Vafaeipour et al, 2022;Wang et al, 2022). The beneficial properties of herbs on the productivity of poultry may be associated with the release of digestive enzymes secretions, thereby improving feed consumption and enhancing growth performance (Darmawan et al, 2022;Latek et al, 2022). Amongst these, curcumin is a bioactive polyphenolic constituent that exhibits antimicrobial, anti-inflammatory, anti-carcinogenic, anti-proliferative, and antioxidant actions Swelum et al, 2021;Hafez et al, 2022;Li et al, 2022).…”
mentioning
confidence: 99%